Aggressive Drive Derivatives in the Rorschachs of Maltreated Children and Adolescents: Latent Structure and Clinical Correlates. Issue 6 (2nd November 2017) - Joubert, David; Webster, Linda
ABSTRACT: Psychological assessment can play an important role in informing the intervention process with child and adolescent victims of maltreatment. This study investigated the validity of the Rorschach in assessing aggressive drive derivatives using a profile-based approach, with a sample of 108 children and adolescents in foster care. Aggression indicators were derived from the work of Gacono and Meloy (1994 ). Latent class analysis yielded a 4-class model including gender and age as covariates. The first 2 classes were characterized by low prevalence rates across all indicators of aggression, and were distinguished primarily on the basis of participant's age. The 3rd class was characterized by the presence of Aggressive Vulnerability (AgV) responses, whereas the 4th showed higher occurrence of all markers except AgV. Modest associations were found between characteristics of abuse, select classes, and behavior problems. The 4th class showed the strongest link with behavior problems, albeit only in the presence of ego impairment. These findings support a contextualized, developmentally informed use of aggression markers on the Rorschach in the context of child maltreatment.